2020
DOI: 10.1155/2020/5013898
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Herb‐Drug Interaction between Hibiscus sabdariffa Calyces Aqueous Extract and Captopril in Rats

Abstract: Hibiscus sabdariffa L. (Malvaceae) is a traditional medicinal herb widely consumed as a beverage (“hibiscus tea”), and its global popularity is expanding due to health benefits such as blood pressure and cholesterol control. Previous studies showed that Hibiscus sabdariffa is coadministered with antihypertensives and antihyperlipidemics, thus predisposing herb-drug interactions. We investigated the pharmacokinetic interaction between H. sabdariffa L. aqueous extract and captopril, a frequently prescribed antih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
(43 reference statements)
0
1
0
1
Order By: Relevance
“…Aldosteron akan menyebabkan terjadinya vasokontriksi berupa peningkatan penyerapan kembali natrium dan peningkaran cairan ekstraseluler sehingga hal tersebut dapat menyebabkan retensi cairan dimana terjadi peningkatan volume cairan ekstraseluler dan peningkatan tekanan darah di dalam arteri yang menyebabkan tingginya tekanan darah pada penderita hipertensi [27]. Antosianin, asam organik (hibiscus acid dan asam hidroksisitrat), asam fenolik, asam linoleat serta flavonoid (gossypetin, hibiscetin, kaempferol dan kuersetin) merupakan senyawa kimia yang terbuki terkandung dalam bunga rosela dan dapat menghambat perubahan angiotensin I menjadi angiotensin II [4,6,10,11,12,14,16,23,24]. Berdasarkan penelitian Salem dkk.…”
Section: Hasil Dan Pembahasan 31 Pencarian Literaturunclassified
“…Aldosteron akan menyebabkan terjadinya vasokontriksi berupa peningkatan penyerapan kembali natrium dan peningkaran cairan ekstraseluler sehingga hal tersebut dapat menyebabkan retensi cairan dimana terjadi peningkatan volume cairan ekstraseluler dan peningkatan tekanan darah di dalam arteri yang menyebabkan tingginya tekanan darah pada penderita hipertensi [27]. Antosianin, asam organik (hibiscus acid dan asam hidroksisitrat), asam fenolik, asam linoleat serta flavonoid (gossypetin, hibiscetin, kaempferol dan kuersetin) merupakan senyawa kimia yang terbuki terkandung dalam bunga rosela dan dapat menghambat perubahan angiotensin I menjadi angiotensin II [4,6,10,11,12,14,16,23,24]. Berdasarkan penelitian Salem dkk.…”
Section: Hasil Dan Pembahasan 31 Pencarian Literaturunclassified
“…46,47 It has been shown that co-administration of HS aqueous extract can change the Pharmaceutical Sciences (Indexed in ISI and Scopus) https://ps.tbzmed.ac.ir pharmacokinetic profile of captopril; for that reason, its co-administration should be avoided. 48 Several studies have indicated that HS extracts can reduce the levels of TG, Tc, LDLc, and LDLc/HDLc in humans and animal models. 49 The aqueous extract of HS lowered Tc better than simvastatin and improved antihyperlipidemic activity when co-administered at low doses in an animal model.…”
Section: Hibiscus Sabdariffa Pharmacokineticmentioning
confidence: 99%